DC's legends of tomorrow. The complete first season [videorecording (DVD)] - Berlanti, Greg; Guggenheim, Marc; Kreisberg, Andrew, 1971-; Klemmer, Phil (Warner Home Video, 2016)
When heroes alone are not enough, the world needs legends. Having seen the future, traveling rogue Rip Hunter assembles a disparate group of both heroes and villains to confront the unstoppable threat of the immortal Vandal Savage, a threat which not only puts the planet at stake, but all of time itself. From the creators of The Flash and Arrow come this super hero team-up that combines characters from both shows.